SELF-MANAGEMENT AND WORK READINESS AMONG BACHELOR’S DEGREE FRESH GRADUATES - utami, Narastri insan; Siti Yuliany (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
A graduate is generally expected to possess stronger competencies than a non-graduate, particularly at the undergraduate level, where higher education should foster greater competitiveness and work readiness to meet industry standards. However, many fresh graduates report feeling unprepared to enter the workforce, and employers frequently perceive them as lacking essential readiness for work. This study aims to examine the relationship between self-management and work readiness among fresh graduates of undergraduate programs. The proposed hypothesis states that there is a positive relationship between self-management and work readiness. The study involved 120 fresh graduate participants. Research data were collected using the Work Readiness Scale (reliability coefficient = 0.883) and the Self-Management Scale (reliability coefficient = 0.900). Data analysis was conducted using the Product Moment correlation technique. The results show a correlation coefficient of r = 0.846 with p = 0.000 (p < 0.050), indicating a significant positive relationship between self-management and work readiness among fresh graduate undergraduate students.